2020
DOI: 10.1617/s11527-020-01561-1
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous and drying shrinkage of mortars based on Portland and calcium sulfoaluminate cements

Abstract: Calcium sulfoaluminate (CSA) cement can be used as an alternative binder in concrete, partially or fully replacing ordinary Portland cement. While CSA cement considerably accelerates the mechanical properties development, the rapid evolution of the microstructure together with the high water demand cause rapid and large volume changes at early ages. As volume changes may lead to early-age cracking, measures to reduce them may be required In this paper, autogenous and drying shrinkage are studied in mortars pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…It is consistent with the shrinkage phenomenon of AAS containing WG for which a rapid early autogenous and drying shrinkage is typical [7,16,17]. In the case of H material, it can be stated that the shrinkage process is very similar to OPC materials [18]. The difference in shrinkage between the WG and H material origins from the hydration kinetics and pore size distribution which differ substantially for both materials [19,20].…”
Section: Resultssupporting
confidence: 74%
“…It is consistent with the shrinkage phenomenon of AAS containing WG for which a rapid early autogenous and drying shrinkage is typical [7,16,17]. In the case of H material, it can be stated that the shrinkage process is very similar to OPC materials [18]. The difference in shrinkage between the WG and H material origins from the hydration kinetics and pore size distribution which differ substantially for both materials [19,20].…”
Section: Resultssupporting
confidence: 74%
“…In nonproprietary ternary blended systems, the proportions of the binder composition can be categorized in three forms—(i) PC‐rich system where PC amount is higher compared to CAC or CSA; (ii) CAC‐rich CAC–PC–C$ blended system where CAC amount is higher than PC, and (iii) CSA‐rich CSA–PC–C$ blended system where CSA amount is higher than PC. So far, most of the studies have investigated PC‐rich systems as shown in Figure 3 12,19,22,34,35,38,39,43,48,61,68–82 . Most of the previous studies were conducted on PC‐rich CAC or CSA systems.…”
Section: Binder Compositionmentioning
confidence: 99%
“…Similarly, the CSA mixture only released 0.01 mL/g of sample during the pore solution extraction procedure and the OPC and Blend mixtures released around 0.02 mL/g of sample. Greater self-desiccation has been well documented in CSA hydration and is a practical advantage for some building applications where "fastdrying" is desired [6]. Drying due to evaporation during sample storage and handling resulted in negligible mass loss.…”
Section: Interpreting the Electrical Propertiesmentioning
confidence: 99%
“…Ettringite binders rapidly consume water during hydration (e.g. internal drying), and this could lead to greater electrical resistivity than an OPC sample that maintains a higher internal relative humidity [6,7]. However, methods have been developed to correct for varying levels of saturation in resistivity measurements [8].…”
Section: Introductionmentioning
confidence: 99%